Enhanced Financial Mechanisms for Post 2012 Mitigation - Figueres, Christiana; Streck, Charlotte (2012)
Despite the many calls to reform the CDM, its conceptual underpinnings are strong and it will most likely survive in the post-2012 climate regime. Some modifications may be considered in the short term to strengthen the effectiveness and transparency of the mechanism without modifying the Marrakesh Accords. In the medium term substantially increased mitigation efforts in developing countries may require a combination of three possible financial mechanisms: the current activity-based CDM albeit improved, a second market mechanism that would seek to improve the long term emission trends of developing countries by promoting broad based emission reduction programs primarily in the private sector, and a third financial mechanism outside of the market which would be an incentive for the adoption of policy changes leading to a low carbon path, but where emission reductions would not be used as international offsets.